Adolescent substance use: Findings from a state-wide pilot parent education program - Nayantara Nair; Alishia Elliott; Sarah Arnold; Andrew Flachs; Barbara Beaulieu; Kristine Marceau (BMC, 2022)
Abstract Background Adolescent substance use has long been a top public health priority. In Indiana, concerning recent trends show high rates of youth alcohol consumption coupled with increasing use of opioids, synthetic marijuana, and over-the-counter drugs. Based on research indicating that parent-based prevention efforts may be a particularly effective way to target adolescent substance use, and in a direct effort to address Indiana's 2017 Strategic Plan to Address Substance Use, we conducted an applied research study targeting parents' knowledge regarding adolescent substance use in Indiana. Methods This community-based applied research study included: (i) a needs assessment of Indiana Extension Educators' concerns regarding adolescent substance use, (ii) creation and dissemination of an evidence-informed parent education program on adolescent substance use in collaboration with Purdue Extension (a key community stakeholder), and (iii) qualitative focus group discussions at the end of each program that assessed the challenges families face regarding adolescent substance use, the types of information and resources they wish they had, and the usefulness of our program. Results The needs assessment revealed that Indiana communities would most benefit from education regarding ways to spot and monitor substance use in teens, and strategies to communicate with teens about substance use. Additionally, Extension Educators thought that existing resources to tackle substance use largely did not match the needs of Indiana communities. Qualitative analysis of the focus group discussions across 8 pilot programs revealed five important themes: (1) The need for current, evidence-informed information regarding adolescent substance use among parents and youth-involved professionals in Indiana, (2) Concern regarding Indiana adolescents' ease of access to substances and lack of healthy recreational activities, (3) Communicating with teens about substance use is crucial but difficult to implement, (4) Indiana communities' need to prioritize funding for evidence-informed prevention programming, and (5) The need for community-based parent and caregiver support groups. Conclusions Overall, the program was well-received and participants indicated that there was a strong need for this programming in their communities, but suggested collaborating with schools or similar local community stakeholders to increase attendance. Findings from this pilot study can inform future community-based adolescent substance use prevention efforts state-wide.